Gender and labour market inclusion on the island of Ireland - Garance Hingre; Helen Russell; Frances McGinnity; Emer Smyth (The Economic and Social Research Institute (ESRI), 2024)
Labour market inclusion is a key component of gender equality. In recent decades, in Ireland and Northern Ireland, women have increasingly entered paid employment. Yet, comparative research across the island on the level and conditions of women's participation remains limited. Different policies, educational systems, sectoral distribution of employment, attitudes to equality, migration and economies shape the participation and inclusion of women in the labour market, with notable differential consequences for gender equality North and South on the island of Ireland. This report draws on a consultation with key stakeholders and analysis of labour force survey data to identify the barriers and opportunities to women's participation on the island of Ireland. In both jurisdictions, it explores the impact of policies, education, demographic characteristics, household types, sectors, and attitudes on the participation and conditions of women and men in the labour market.
Keywords: 330; Weibliche Arbeitskräfte; Arbeitsmarktdiskriminierung; Geschlechterdiskriminierung; Vergleich; Irland; Nordirland